Effects of Distillers Dried Grains with Solubles Sources and Soybean Meal Level on Growth Performance of Late Nursery Pigs - H. S. Cemin; M. D. Tokach; A. M. Gaines; B. W. Ratliff; E. L. Hakmiller; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
Two experiments were conducted to determine the effects of distillers dried grains with solubles (DDGS) source and soybean meal (SBM) level on growth performance of late nursery pigs. A total of 1,064 and 1,011 pigs (PIC 280 × 1050), initially 23.1 and 24.1 lb body weight (BW), were used in Exp. 1 and 2, respectively, with 21 to 27 pigs per pen. For approximately 21 days after weaning, pigs were fed common phase 1 and 2 diets. Then, pens were assigned to treatments in a randomized complete block design. There were 6 treatments in each experiment with 7 pens per treatment. Treatments 1 to 5 were replicated in Exp. 1 and 2, whereas treatment 6 was fed only in Exp. 1 and treatment 7 was fed only in Exp. 2. Treatments 1 to 3 consisted of diets with 23% conventional DDGS (Valero, Aurora, SD) and 21, 27, or 35% SBM. Treatments 4 and 5 were corn-SBM-based diets with 27 or 35% SBM. Treatment 6 consisted of a corn-SBM-based diet with 20% high protein DDGS (HP DDGS; Purestream 40, Lincolnway Energy, LLC, Nevada, IA) replacing the 23% conventional DDGS with the same amount of SBM (21%) as treatment 1 and same neutral detergent fiber (NDF) as treatment 2. Finally, treatment 7 consisted of a diet similar to treatment 2 but with 23% Lincolnway DDGS (Lincolnway Energy, LLC, Nevada, IA) replacing the 23% conventional DDGS. Data were analyzed with the GLIMMIX procedure of SAS. There was no evidence for treatment × experiment interactions, thus data from treatments 1 to 5 were combined. In Exp. 1, pigs fed diets containing HP DDGS had decreased (P<0.01) average daily gain (ADG) and poorer (P<0.01) feed-to-gain ratio (F/G) compared to pigs fed diets with conventional DDGS at the same NDF level, conventional DDGS at the same SBM level, or corn-SBM diet. In Exp. 2, there was no evidence for differences (P>0.10) in performance of pigs fed diets with Lincolnway DDGS or conventional DDGS. Feeding diets with 23% conventional DDGS decreased (P= 0.033) average daily feed intake (ADFI) and improved (P= 0.033) F/G compared to corn-SBM-based diets. Finally, ADG increased (linear,P= 0.001) and F/G improved (quadratic,P= 0.007) as SBM level increased from 21 to 35%. In conclusion, decreased growth performance indicates that the nutrient profile of the HP DDGS may have been overestimated. The net energy of conventional and Lincolnway DDGS seemed to be underestimated due to the improved F/G compared to corn-SBM diets. Finally, feeding diets with increasing SBM resulted in improved growth performance in late nursery pigs.
Keywords: distillers dried grains; growth performance; nursery pig; soybean meal